(untitled) (Journal of Computational Mathematics, 2021)
When one compares a difference scheme with another, only a qualitative comparison is usually given. Such a comparison is not enough. For example, Scheme A is more accurate than Scheme B, but it would take more time to use Scheme A than to use Scheme B. In order to determine which scheme is the best, it is necessary to make a quantitative comparison among difference schemes.